The Efficacy of Flipped Classroom Models in Improving Student Engagement and Achievement: A Meta-Analysis - Azlinda Zainal Abidin , Noor; Mislave, Benić; Abenue Asefuaba, Yalley; ABIDIN, NOOR (Global Synthesis in Education Journal, 2024)
The educational landscape continues to evolve in response to shifting student needs and technological advancements. The flipped classroom model has garnered significant attention as a potentially transformative approach to teaching and learning, yet inconsistencies in research findings necessitate a systematic analysis of its effectiveness. This meta-analysis aimed to quantify the effectiveness of flipped classroom approaches on student engagement and academic achievement, identify key moderating variables, and develop evidence-based implementation recommendations. A comprehensive meta-analysis of 172 studies published between 2010-2024 was conducted, employing rigorous inclusion criteria and standardized coding procedures. Random effects models were used to calculate aggregate effect sizes and conduct moderator analyses to examine variables influencing effectiveness. The results of this meta-analysis indicate that flipped classroom approaches demonstrate a medium positive effect on student engagement (g = 0.57) and a small-to-medium effect on academic achievement (g = 0.42). Behavioral engagement (g = 0.63) and cognitive engagement (g = 0.59) showed stronger effects than emotional engagement (g = 0.48). Effectiveness varied by subject domain, with stronger effects in STEM (g = 0.49) and professional disciplines (g = 0.46). An inverse relationship emerged between educational level and effect size, with primary education showing the strongest effects (g = 0.58). Implementation duration (r = 0.42) and quality significantly moderated outcomes, with high-quality implementations demonstrating substantially stronger effects than low-quality implementations. This research resolves inconsistencies in current literature by systematically quantifying effectiveness across contexts and identifying influential moderating variables, providing educational stakeholders with evidence-based implementation guidance. The findings of this meta-analysis indicate that flipped classroom approaches consistently enhance student engagement and achievement across educational contexts. Implementation effectiveness is significantly influenced by educational level, subject domain, implementation duration, and quality. Educational stakeholders should prioritize comprehensive implementation planning and sustained support to maximize effectiveness, particularly in primary and secondary education settings.